Computational simulation of TEVAR in the ascending aorta for optimal endograft selection: A patient-specific case study. (1st December 2018) - Romarowski, R.M.; Conti, M.; Morganti, S.; Grassi, V.; Marrocco-Trischitta, M.M.; Trimarchi, S.; Auricchio, F.
Abstract: Thoracic endovascular aortic repair of the ascending aorta is becoming an option for patients considered unfit for open surgery. Such an endovascular procedure requires careful pre-operative planning and the customization of prosthesis design. The patient-specific tailoring of the procedure may call for dedicated tools to investigate virtual treatment scenarios. Given such considerations, the present study shows a computational framework for choosing and deploying stent-grafts via Finite Element Analysis, by supporting the device sizing and selection in a real case dealing with the endovascular treatment of a pseudoaneurysm. In particular, three devices with various lengths and materials were examined. Two off-the-shelf devices were computationally tested: one composed of Stainless Steel rings with a nominal length of 60 mm and another one with Nitinol rings and a distal free flow extension, with a nominal length of 70  mm . In third place, a custom-made stent-graft, also with Nitinol rings and containing both proximal and distal bare extensions with a nominal length of 75 mm, was deployed. The latter solution based on patient morphology and virtually benchmarked in this simulation framework, enhanced the apposition to the wall by reducing the distance between the skirt and the vessel from more than 6  mm to less than 2  mm in the distal sealing zone. Our experience shows that in-silico simulations can help choosing the right endograft for the ascending aorta as well as the right deployment sequence. This process may also encourage vendors to develop new devices for cases where open repair is unfeasible. Highlights: Stent-graft customization provides better treatment than off-the-shelf devices. Wall apposition improves when design is tailored with patient-specific simulations. Realistic simulations necessarily need to resemble the actual deployment sequence. Virtual tools to support endovascular planning in the aorta are ready to be used.